The stubbornness of authoritarianism: autocracy-to-autocracy transitions in the world between 2000 and 2015. (14th May 2019) - Del Panta, Gianni
Abstract: Whilst much of the contemporary debate on regime change remains concentrated on transitions to and from democracy, this paper focuses on autocracy-to-autocracy transitions, a relatively understudied but particularly relevant phenomenon. Building on an updated typology of non-democratic regimes and through a qualitative case-by-case assessment, the present paper identifies 21 transitions from one dictatorship to another, out of 32 cases of autocratic breakdown during the 2000–15 period. Hence, after the fall of a dictatorship, the installation of a new authoritarian regime was almost twice as likely as democratization. Accordingly, the paper focuses on the 21 recorded autocracy-to-autocracy transitions and examines in which non-democratic regimes a transition from an autocracy to another is more likely to occur, which peculiar forms of authoritarian rule tend to be installed, and the specific ways in which the dismantling of the previous existing authoritarian rule is achieved.